Tax-induced clientele effects in the market for British government securities - Schaefer, Stephen M. (Journal of Financial Economics, 1982)
This paper develops a new methods for measuring tax effects in bond markets and presents empirical results for British Government Securities. The basic idea is to construct a least cost portfolio which, for investors in a given tax bracket, dominates a given bond. A portfolio is said to dominate a bond if it provides cash flows which are at least as great in every period, and has a lower price. In effect our method calculates an upper bound on the value of a bond to investors in a given tax bracket. The results demonstrate (i) the existence of clientele effects and (ii) the absence of an ‘effective tax rate’.